Band‐stop filter based on spoof surface plasmon polaritons. Issue 10 (1st May 2019) - Zhao, Lei; Liu, Shuang; Wang, Jun; Shen, Xiaopeng; Cui, Tie Jun
Abstract : A band‐stop filter based on spoof surface plasmon polaritons for microwave applications is proposed, which can realise high‐efficiency band rejections by etching gradient semi‐circular grooves on both sides of the middle stripline of coplanar waveguide. The operating bandwidth and frequency of band‐stop can be controlled by changing the radii of semi‐circular holes and the length of unit cell, respectively. The operating principle of the designed band‐stop filter is explained by the dispersion curves and electric field distributions. Parametric studies are also conducted to analyse the effects of key parameters on the performance of the band‐stop filter, which is useful for practical designs. A prototype of the band‐stop filter is fabricated and measured. The good agreements between the simulated and measured results validate the proposed design, which indicate that the presented band‐stop filter can be potentially useful in many microwave applications.